15. Cardiac magnetic resonance imaging damages evaluation using T1 values and apparent diffusion coefficient in left-sided breast cancer radiotherapy: A case report. (December 2018) - Belligotti, E.; Coniglio, A.; Abella, A.; Della Longa, G.; Mazzarella, G.; Bufacchi, A.; Di Renzi, P.
Abstract : Purpose: Clinical importance of radiation-induced heart disease (RIHD) has been recognized only recently[1] . RIHD is not extensively studied because of the latent period; his pathological expressions include acute and chronic pericarditis, myocardial fibrosis and late ischemic cardiomyopathy. To evaluate RIHD in a patient who underwent radiotherapy treatment (RT) for left-sided breast cancer, cardiac magnetic resonance imaging (CMRI) was performed and myocardial T1 and apparent diffusion coefficient (ADC) calculated. Methods: A woman 43 y with left-sided breast cancer, underwent chemo-RT treatment with a total dose of 50 Gy. FEVS remained constant (70%) pre, during and post RT. The patient received a mean dose of 3.5 Gy to the heart. Cardiac morphological and functional evaluation was executed performing CMRI before RT, after 9 irradiations and 1 month later the end of RT. Single slice axial echo planar imaging (EPI) with b-values equal to 0–350 s/mm 2 and 3-dimensional inversion recovery sequences were used to calculate, respectively, myocardial ADC and T1 values using a bespoke MATLAB®code. Reported T1 represents the mean T1 value calculated over 10 slices acquired in short axis view. Except for the acquisition performed during RT, T1 values were evaluated after intravenous contrast medium administration. Results: We found a reduction of myocardial mean T1 value from 547 ± 40 ms pre-RT to 473 ± 35 ms post-RT, with lower value in apical region (434 ± 26 ms). ADC maps shows a reduction of 50% of ADC value (3.0 ± 1.6 μm 2 /ms) during irradiation and confrontable value pre-RT (6.3 ± 0.9 μm 2 /ms) and post-RT (6.1 ± 1.3 μm 2 /ms). Conclusions: Our results show a reduction of T1 value after irradiation that could be referred to a possible asymptomatic early state of diffuse fibrosis. A variation of ADC during RT could be associated to a possible inflammatory condition that could be recovered 1 month after RT.